Integrated communication model for the propagation of Buddhist principles in Thailand (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of this research (1) is to study the factors affecting the integrated communication for the propagation of Buddhist principles and (2) to establish and verify the consistency of a causal relationship model with empirical data, integrative communication that influences Buddhist philanthropy. Using quantitative and qualitative research methods, It starts with the examination of empirical data from real experiences with the theoretical framework established by the researcher from the principles, concepts and theories in order to obtain important findings in the study of the Integrated communication model for the propagation of Buddhist principles in Thailand. Data were collected by questionnaires from 400 Buddhist subjects who practice Dharma at the provincial religious practice bureau. The data were used for structural equation modeling (SEM) analysis and in-depth interviews with 9 experts to confirm the study results.The results show that (1) the results of the study showed that the Brand Orientation, Market Orientation and Consumer Characteristics have a positive influence on integrated communication for the spread of Buddhist principles and the merit making of Buddhists. (2) Integrated communication for the spreading of Buddhist principles has a positive influence on Buddhist merit-making. (3) The model was consistent with empirical data based on the six indexes that met the acceptance criteria: c2/df =1.319, P = 0.058, RMSEA= 0.028, SRMR=0.017, GFI=0.975 and AGFI= 0.952. The model consists of 5 main components and 14 sub-elements as follows: (1) Brand Orientation has 3 components: Shared brand vision, Brand value-adding capability and Shared brand positioning (2) Market Orientation has 3 components: Customer Orientation, Competitive Orientation and Interfunctional Coordination. (3) Consumer Characteristics has 3 components: Motivation, Ability and Opportunity. (4) Integrated communication has 2 components: Traditional media and newer online media and (5) Performance has 3 components: Giving Alms, Precept undertaking and Bhavana.